2020
DOI: 10.1371/journal.pone.0231805
|View full text |Cite|
|
Sign up to set email alerts
|

Soil applied boron (B) improves growth, yield and fiber quality traits of cotton grown on calcareous saline soil

Abstract: Boron (B) is required during all growth stages of cotton crop, especially during boll formation. However, Typic Haplocambid soils of cotton growing belt in Pakistan are B-deficient, which results in low yield and economic returns. Foliar application of B improves cotton productivity; however, information is limited on the role of soil applied B in improving cotton growth and yield. The current study investigated the role of soil applied B in improving growth, yield and fiber quality of cotton crop. Five differ… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 44 publications
5
11
0
Order By: Relevance
“…With further surge in boron application 0 rate, the augmentation in seed cotton yield stayed statistically similar with preceding application rates. Similar findings were also reported in earlier research(Atique-ur-Rehman et al, 2020;…”
supporting
confidence: 93%
See 2 more Smart Citations
“…With further surge in boron application 0 rate, the augmentation in seed cotton yield stayed statistically similar with preceding application rates. Similar findings were also reported in earlier research(Atique-ur-Rehman et al, 2020;…”
supporting
confidence: 93%
“…Boron is conveyed from the roots to the shoot via xylem by mass flow under power of transpiration tug (Kochian, 1991) and amasses higher quantity of B at the tips and margins of older leaves than in other parts of plant. These outcomes are in compliance to earlier research findings that showed that increased B concentration was ascribed to enhance absorption of soil applied B, and its accumulation in different vegetative plant parts under influence of transpiration tug (Boparai and Manchanda, 2019;Atique-ur-Rehman et al, 2020). The non-uniform allocation of B among different parts of cotton in our experimental outcomes has been ascribed to its immobile nature or very limited mobility in phloem of cotton (Gormus and Barutcular, 2016;Boparai and Manchanda, 2019).…”
supporting
confidence: 92%
See 1 more Smart Citation
“…Our results buoyed the hypothesis that seed priming with B can improve seedling emergence, growth and development, grain yield and related traits, grains B concentration and grain quality of mungbean (Tables 1 – 3 and Figs 1 – 4 ). Boron deficiency is growing and creating a stern problem in calcareous soils (hyperthermic, sodic haplocambids) [ 6 ]. Application of B seed priming @ 0.01% significantly (p≤0.05) improved the growth and yield-related characteristics of tested mungbean cultivars.…”
Section: Discussionmentioning
confidence: 99%
“…A careful diagnosis is indebted to a narrow range for B deficiency and its toxicity for all crops [ 5 , 6 ]; therefore, its application amount/concentration is very critical. However, B-deficiency could be corrected in several ways.…”
Section: Introductionmentioning
confidence: 99%